Gaze from motion: Towards natural user interfaces - Jeong, MH; Ohsugi, M; Funayama, R; Mori, H (SPRINGER-VERLAG BERLIN, 2004)
We propose a method of 3-D gaze estimation allowing the head motion under an uncalibrated monocular camera system. The paper describes the eyeball structure model with compact descriptions of the eyeball motion and its static 3-D structure. Assuming that the eyeball motion is independent of the head motion, we present a dynamic converging-connected model to make the gaze estimation allowing the head motion more systematic and simple. The gaze estimation is performed through the extended Kalman filter using the eyeball structure model and the dynamic converging-connected model. The preliminary test suggests satisfactory results.
Keywords: EYE